METABOLIC SYNDROME WITH CORONARY HEART DISEASE ON ELDERLY - Intan Putri Prayitno (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Obesity, insulin resistance, dyslipidemia, and hypertension are the main components of the metabolic syndrome. Cardiovascular disease (CVD) is the leading cause of mortality and morbidity in developed countries and developing. The aim of this study is to diagnose the disease, know the causes, the risk factors, the management, and to improve patient outcomes and increase patient knowledge along with awareness about the disease and the metabolic syndrome, especially coronary heart disease. Descriptive study in the case reports with data obtained derived from primary data obtained through anamnesis, physical examination andlaboratory tests. Home visits for intervention and assessment of outcomes. Men, 65 years old, diagnosed with metabolic syndrome. Blood pressure was 200/110 mmHg, 68x pulse/minute, respiratory rate was 23x/min, temperature was 36,50C, 150 cm of height, 75 kg of weight and the BMI was 33.33, waist length was 104 cm, at time blood glucose was 368 g/dl, had a history of recurrent chest pain. With the risk factors of smoking, lack of activity, and bad diet pattern. After the intervention there was improvement on knowledge of patients disease, decrease blood pressure and blood sugar level. [J Agromed Unila 2014; 1(2):156-160]Keywords: cardiovascular desease, lifestyle, metabolic syndrome